Choosing the exchange rate regime – a case for intermediate regimes for emerging and developing economies - Jurek, Michał (Economics and Business Review, 2018)
The main objective of the paper is to verify the vanishing interim regime hypothesis(so-called bipolar view) and to analyse factors that may influence the probabilityof use of intermediate exchange rate regimes, especially in emerging and developingeconomies. In order to accomplish the research objectives the evolution of exchangerate regimes is presented with the special consideration of decisions of IMF memberstates in this respect. Next a logistic regression model that estimates the probability ofuse of an intermediate regime is applied. The results achieved allow a challenge to thevanishing interim regime hypothesis. Empirical observations support this hypothesisonly in advanced countries and not in their emerging and developing peers.